Evaluation of Supply Chain Performance through Integration of Hierarchical Based Measurement System and Traffic Light System: A case Study Approach to Iron Sheet Factory - Abdul Mail; Nurul Chairany; Asrul Fole (International Journal of Supply Chain Management, 2019)
Some of literature shows that the SCM model is effective enough in evaluating and measuring whether the enterprise is went well, efficient and effective. Nevertheless, the available literature is still quite limited in offering perspective in integrating various methods in evaluating and the measurement of SC performance easily and simply. The SCOR model as one of approach in measuring the SC performance, operationally still need to be integrated with another approach. This was intended to reveal the clarity of the target and the result of measurement in more effectively, comprehensively, and accountably. In this study, it would be conduct a measurement of SC performance of iron sheet factory enterprise within using the SCOR model through the hirarchial integration based measurement system with traffic light system. The result of this study suggests that such integration can provide solutions for management of evaluation and measurement of enterprise's performance in a more effectively, comprehensively, accountably and integrated.